Study of Different Personalised Dietary Plans on Eating Behaviour, Body Image and Mood in Young Female Professional Handball Players: A Randomised Controlled Trial - Laura Miralles-Amorós; Manuel Vicente-Martínez; María Martínez-Olcina; Nuria Asencio-Mas; Lucía Gonzálvez-Alvarado; Marcelo Peñaranda-Moraga; Belén Leyva-Vela; Rodrigo Yáñez-Sepúlveda; Guillermo Cortés-Roco; Alejandro Martínez-Rodríguez (MDPI AG, 2023)
Low energy availability may precede or be caused by cognitive disturbances in professional athletes. Related psychological problems include disordered eating patterns, body shape preoccupation, depression or anxiety. The objective of this research was to evaluate the effects of different personalised dietary plans on psychological factors in young professional female handball players with low energy availability. This 12-week randomised clinical trial involved 21 female players aged 22 ± 4 years, 172.0 ± 5.4 cm and 68.4 ± 6.7 kg divided into three groups (FD: free diet; MD: Mediterranean diet; HAD: high antioxidant diet). Eating behaviour (Eating Attitude Test, EAT-26: diet, bulimia and oral control subscales), body image (Body Shape Questionnaire, BSQ) and mood state (Profile of Mode State, POMS: tension, vigour, anger, depression, fatigue) were assessed. All participants showed low energy availability (<30 kcal/lean mass per day). The different plans showed no significant differences between them but significant differences over time within groups for the variables: body image, Tension, Vigour and Depression (p < 0.05). Eating behaviour improved slightly but did not show statistically significant changes. Following an adequate nutritional planning for athletes seems to improve the mood and body perception of young female handball players. A longer intervention period is required to assess the differences between diets and improvement of other parameters.